FINANCIAL PERFORMANCE ANALYSIS OF THE MULTI-FUNDS FROM 2002 - 2010 - Mussatto, Alejandro Torres; Mayne, Eric Salinas (European Scientific Journal, ESJ, 2014)
This paper evaluates, in a strictly financial manner, the performance obtained by the social security multi- funds in Chile from their inception to 2010. The first protective labor legislations were passed under the Partial Capitalization System that was sustained by the active contributors who financed the pensions of the passive. This System was radically modified to an Individual Capitalization System through pension reforms made in the 1980s. The income earned in the passive phase of working life were in direct relation with the individual contributions from the members, not guaranteeing return under a private administration. The legislation did not suffer major modifications until 2002. It included a system of multi-funds in which the management company of the resources contributed by the workers offered the possibility of investing those resources in aggressive portfolio based on their age. After almost 10 years, we wonder if those funds that are the only income in the vast majority of the cases were efficiently managed by these private companies because, in addition to the mandatory contribution percentages, there are certain payments the contributors must withstand: management services known as commissions. Through the implementation of certain financial metrics, the results indicate that earnings have not experienced abnormal returns. Also, the reference market portfolios in many findings show us better yields than those offered by these companies.